Grounding of Concept, Indexical, and Name - Hausser, Roland (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2021)
The semantics of agent-based DBS is ‘grounded’ in that the Content kinds concept, indexical, and name have their foundation in the agent’s recognition and action, whereby each Content kind has its own computational Mechanism. For a concept it is pattern matching between the type provided by memory and raw data provided by the agent’s interface component. For an indexical it is pointing at a STAR value of the agent’s on-board orientation system (OBOS). For a name it is the address of the ‘named referent’ which is inserted as the core value into a lexical name proplet in an act of baptism. Orthogonal to the Content kinds and their computational Mechanisms are the Semantic kinds referent, property, and relation with their associated Syntactic kind noun, adj and intransitive verb, and transitive verb. It is shown that the Semantic kind of referent is restricted to the Syntactic kind of noun, but utilizes the computational Mechanisms of matching, pointing, and baptism. Furthermore, figurative use is restricted to the computational Mechanism of matching, but uses the Semantic kinds referent, property, and relation.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Computational mechanisms of matching; pointing; baptism; Content kinds of concept; indexical; name; Language vs. nonlanguage content; Recognition vs. action; Semantic kinds of referent; property; relation; Speak mode vs. hear mode; Syntactic kinds of noun; adj; verb; Type vs. token